2024
DOI: 10.1021/acssynbio.4c00111
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a High-Yield Chloroplast Cell-Free System for Prototyping Genetic Parts

Lauren Clark,
Christopher A. Voigt,
Michael C. Jewett

Abstract: Plastid engineering offers the potential to carry multigene traits in plants; however, it requires reliable genetic parts to balance expression. The difficulty of chloroplast transformation and slow plant growth makes it challenging to build plants just to characterize genetic parts. To address these limitations, we developed a high-yield cell-free system from Nicotiana tabacum chloroplast extracts for prototyping genetic parts. Our cell-free system uses combined transcription and translation driven by T7 RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Our study successfully demonstrated the development of CFE systems from the chloroplasts of spinach, wheat, and poplar, demonstrating that a previously developed protocol for tobacco is versatile across species. We also showcased the potential for native transcription and the characterization and prototyping of regulatory sequences at both transcription and translation levels.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Our study successfully demonstrated the development of CFE systems from the chloroplasts of spinach, wheat, and poplar, demonstrating that a previously developed protocol for tobacco is versatile across species. We also showcased the potential for native transcription and the characterization and prototyping of regulatory sequences at both transcription and translation levels.…”
Section: Discussionmentioning
confidence: 69%
“…Our objective was to develop a high-yielding CFE system, derived from wheat (a monocot) as well as spinach and poplar trees (dicots). We adapted the workflow for generating highly active cell-free transcription and translation systems from tobacco chloroplasts (Figure S1). In contrast to cell-free expression systems from bacteria, yeast, and mammalian cells, ,,,,, preparation of chloroplast extracts requires separation of an organelle with its own bacteria-like translation machinery from other organelles and subcellular and cytoplasmic components of the plant cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations